Métodos diagnósticos y clasificación de la pancreatitis - Rosales Aguilar, Hugo Francisco (Machala : Universidad Técnica de Machala, 2021)
INTRODUCTION: The pancreas fulfills an important function in the human body such as producing enzymes which helps to digest food, it depends a lot on the care of the patient not to generate pancreatitis that includes severe inflammation and this occurs when enzymes directly damage to the pancreas, likewise acute and chronic pancreatitis develops, for which it depends a lot on the diagnostic methods used such as (Computed Tomography, Ultrasound, Magnetic Resonance, cholangiopancreatography) to verify the severity and complications of the pancreas. OBJECTIVE: To describe the diagnostic methods and classification for pancreatitis through the bibliographic review of scientific articles. METHODS AND MATERIALS: The descriptive study was carried out from the review of scientific articles that help to collect adequate information for the diagnosis of pancreatitis and its classification, which was fulfilled with the exhaustive search for scientific information such as GOOGLE ACADEMIC, PUB-MED, ELSEVIER, SCIELO from the last five years to the present. CONCLUSION: An analysis of the different diagnostic methods was carried out to determine either acute or chronic pancreatitis. Due to the increase in patients with this pancreatic disease, ultrasound is taken into consideration, which is based on the presence of pancreatic and peripancreatic signs, without However, we have other diagnostic methods such as Computed Tomography is more useful to determine the severity and identify complications.
INTRODUCCIÓN: El páncreas cumple una función importante en el cuerpo humano como la de producir enzimas lo cual ayuda a digerir los alimentos, depende mucho del cuidado del paciente para no generar una pancreatitis que comprende una severa inflamación y esto se produce cuando las enzimas dañan directamente al páncreas, así mismo se desarrolla la pancreatitis aguda y crónica por lo cual depende mucho de los método de diagnósticos utilizados como (Tomografía Computarizada, Ecografía, Resonancia Magnética, colangiopancreatografia) para verificar la severidad y complicaciones pancreática. OBJETIVO: Describir los métodos de diagnóstico y la clasificación por pancreatitis a través de la revisión bibliográfica de artículos científicos. MÉTODOS Y MATERIALES: Se realizó el estudio descriptivo a partir de la revisión de artículos científicos que ayudan a la recopilación de información adecuada para el diagnóstico de la pancreatitis y su clasificación, el cual se cumplió con la búsqueda exhaustiva de información científica como GOOGLE ACADEMIC, PUB-MED, ELSEVIER, SCIELO de los últimos cinco años hasta la actualidad. CONCLUSIÓN: Se realizó un análisis de los distintos métodos de diagnóstico para determinar la pancreatitis ya sea aguda o crónica, debido al incrementos de pacientes con esta enfermedad pancreática se toma en consideración la Ecografía que se basa en la presencia de signos pancreáticos y peripancreaticos, sin embargo tenemos otro métodos de diagnóstico como la Tomografía Computarizada es de mayor utilidad para determinar la severidad e identificar las complicaciones.
Keywords: INFLAMACION; PANCREATITIS; ECOGRAFIA; PERIPANCREATICOS